HUBUNGAN ANTARA VERTICAL JUMP, KEKUATAN OTOT PERUT, KELENTUKAN PERGELANGAN TANGAN DAN KECEPATAN SPRINT DENGAN KETEPATAN JUMP SERVICE (STUDI PADA ATLET BOLAVOLI PUTRA PORPROV KABUPATEN SUMENEP) - KURNIAWAN, HENDRA; Irsyada, Machfud (Jurnal Prestasi Olahraga, 2013)
One of Volleyball game techniques is the service motion. One element that is closely related to achievement was the procurement of the service motion. The success of an attack is determined by the accuracy in performing the service. Departing from the idea of the above authors tried to conduct research related to facilitate mastery of the techniques associated with the vertical jump, abdominal muscle strength, flexibility of wrist and speed sprint that can affect the accuracy of the jump serve. The researcher took the research title "The Relationship between Vertical Jump, Abdominal Muscle Strength, flexibility of Wrist and Sprint Speed with the Accuracy of Jump In Serve". The formulation of the problem is how is relationship between the vertical jump, abdominal muscle strength, flexibility of wrist and sprint speed with accuracy jump serve in the men?s volleyball athletes of Porprov Sumenep? Limitations of this study was only conducted on men's Volleyball athletes who follow Porprov Sumenep and only measure the relationship between vertical jump, abdominal muscle strength, flexibility of wrist, and speed sprint jump with jump serve techniques.Based on the research question, then the research was conducted by the research model of correlation analysis or analysis of the relationship that will discuss about which one variable is related to other variables. The dependent variable is the ability of the serve using the jump serve technique. The design used was an asymmetrical relationship of five variables or so-called relationship multivariant. In this study, the population is men volleyball athletes of Porprov Sumenep with a sample is volleyball men's team that competed Porprov Sumenep and this study used the research Purposive Sampling.From the results of the data concluded that the relationship between vertical jump and the accuracy of jump serve is not significant because of its value is 0,012. Vertical jump affects the accuracy of 0,014% jump serve. Abdominal muscle strength of the relationship of the accuracy of the service does not jump significantly because of its value 0,618. Abdominal muscle strength affects the accuracy of the 38% jump serve. Wrist flexibility to the accuracy of the jump serve is not significant because of its value ? 0,241. Wrist flexibility affect the accuracy of 5,8% jump serve. Sprint speed of the accuracy of the jump serve is significant because of its value ? 0,764. Sprint speed affects the accuracy of 58% jump serve. The relationship between vertical jump, abdominal muscle strength, flexibility of wrist and speed sprint to the accuracy of jump serve is not significant because of its value is 0,01. While the magnitude of the contribution of the five variables jointly affect 1% to the accuracy of jump serve